Motywy podejmowania aktywności fizycznej na przykładzie osób trenujących crossfit = Motives on physical activity participation - people training crossfit example - Figaj, Dominika; Poczta, Joanna (Journal of Education, Health and Sport, 2016)
Figaj Dominika, Poczta Joanna. Motywy podejmowania aktywności fizycznej na przykładzie osób trenujących crossfit = Motives on physical activity participation - people training crossfit example. Journal of Education, Health and Sport. 2016;6(6):95-106. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.54711 http://ojs.ukw.edu.pl/index.php/johs/article/view/3541 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 25.05.2016. MOTYWY PODEJMOWANIA AKTYWNOŚCI FIZYCZNEJ NA PRZYKŁADZIE OSÓB TRENUJĄCYCH CROSSFIT MOTIVES ON PHYSICAL ACTIVITY PARTICIPATION - PEOPLE TRAINING CROSSFIT EXAMPLE Dominika Figaj, Joanna Poczta Akademia Wychowania Fizycznego im. E. Piaseckiego w Poznaniu Zakład Kulturowych Podstaw Turystyki Wydział Turystyki i Rekreacji Streszczenie W artykule zaprezentowano zagadnienie aktywności fizycznej odnosząc je do obserwowanego wzrostu uczestnictwa Polaków w tej formie spędzania czasu wolnego. Okazuje się, że nie tylko wzrasta ilość osób systematycznie uprawiających sporty, ale również osób poszukujących nowych from aktywności. Przykładem jest CrossFit. Dlatego postanowiono przeprowadzić badania metodą sondazu diagnostycznego pośród członków poznanskiego klubu Reebok CrosFit Poznań w celu określenia motywów podejmowania tej formy aktywności fizycznej oraz określenia pozytywnych i negatywnych skutków wynikających z jej podejmowania. Okazuje się, że badani są osobami o wysokiej świadomości pozytywnego wpływu regularnie podejmowanej aktywności fizycznej na zdrowie, kondycję i dobre samopoczucie. Słowa kluczowe: motyw, motywacja, aktywność fizyczna, crossfit, sport Abstract The article presents the issue of physical activity by referring it to the observed increase in the Poles participation in this form of leisure. It turns out that not only increases the number of people training sports regularly, but also the number of people looking for new activities. An example is CrossFit. Therefore it was decided to conduct the research by diagnostic survey method among members of the Reebok CrosFit Poznań Club to determine the motives on this form of physical activity, and identify positive and negative impacts resulting from its making. It turns out that the researched group are people with high awareness of the positive impact of regular physical activity on health, fitness and well-being. Keywords: motive, motivation, physical activity, crossfit, sport